1-(2,3,4-Trihydroxybenzylidene)-4-ethylthiosemicarbazide - Shawish, H.B.; Maah, Mohd Jamil; Ng, S.W. (International Union of Crystallography, 2010)
In the title molecule, C(10)H(13)N(3)O(3)S, the thiosemicarbazide =N-NH-C(=S)-NH- fragment is twisted with respect to the aromatic ring [dihedral angle = 20.5 (1)degrees]. A weak N-H center dot center dot center dot S hydrogen bond [3.480 (1) angstrom] links two molecules about a center of inversion to generate a ring. The hydroxy groups are engaged in intermolecular hydrogen bonding; the O-H center dot center dot center dot O and O-H center dot center dot center dot S hydrogen bonds generate a layer motif.